Electrochemical Properties of a Conducting Film Derived from Iron(Ii) Tris(Diaminopolypyridyl) Complex in the S(Iv) Oxoanions Reduction - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L (2011)
A new conducting film derived from the complex [Fe (diaphen)3]2+, (diaphen=5,6-diamino-1,10-phenanthroline) was electropolymerized by cyclic voltammetry onto a glassy carbon electrode. Poly-[FeII (diaphen)3] was studied by cyclic voltammetry, SEM, UV-vis and micro-Raman spectroscopy. Poly-[FeII (diaphen)3] shows electrocatalytic activity in HSO3- reduction in an ethanol/water solution. Electrocatalysis is centered at the ? ring of phenanthroline. Rotating disk electrode studies showed a 0.117V/dec Tafel slope, suggesting an EC process where the electrochemical process is the determining step. The chemical step was studied by UV-vis spectroelectrochemistry. Amperometric behavior showed a linear range between 47.5?M to 417?M and the LOD was 19.5?M. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.